Job search with bidder memories - Carlos Carrillo-Tudela; Guido Menzio; Eric Smith (Federal Reserve Bank of Atlanta, 2009)
This paper revisits the no-recall assumption in job search models with take-it-or-leave-it offers. Workers who can recall previously encountered potential employers in order to engage them in Bertrand bidding have a distinct advantage over workers without such attachments. Firms account for this difference when hiring a worker. When a worker first meets a firm, the firm offers the worker a sufficient share of the match rents to avoid a bidding war in the future. The pair share the gains to trade. In this case, the Diamond paradox no longer holds.
Keywords: J24; J42; J64; 330; job search; recall; wage determination; Diamond paradox; Arbeitsuche; Arbeitsnachfrage; Auktionstheorie; Informationsverhalten; Lohnbildung; Theorie